Is conflicted investment advice better than no advice? - Chalmers, John; Reuter, Jonathan (Journal of Financial Economics, 2020)
The benefit of investment advice depends on the quality of advice and the investor's counterfactual portfolio. We use changes in the Oregon University System Optional Retirement Plan to highlight the impact of plan design on the counterfactual portfolios of advice seekers. When brokers are available and target date funds (TDFs) are not, brokers help participants with high predicted demand for advice bear market risk, but they recommend higher-commission options. When brokers are removed and TDFs are added, new high-predicted-demand participants primarily invest in TDFs, which offer similar market risk but higher Sharpe ratios than the broker-advised portfolios within our sample.